2016
DOI: 10.18203/2320-6012.ijrms20160505
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer awareness and breast self-examination among future female university graduates: comparison between medical and non-medical students

Abstract: INTRODUCTIONBreast cancer is the most common cancer in women in both developed and developing world. It is estimated that 508,000 women died in 2011 due to breast cancer. 1 The incidence of breast cancer is increasing in the developing world due to increase life expectancy, increase urbanization and adoption of western lifestyles. Although some risk reduction might be achieved with prevention, these strategies cannot eliminate the majority of breast ABSTRACTBackground: Breast cancer is a common health problem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…This study stated that, beyond two third of the study subjects revealed to have low overall knowledge toward risk factors, general knowledge, and clinical manifestations of the malignant tumor, which was similar with the reports from Malaysia, Saudi, Egypt, and Nigeria (21, 26–28). Many female students in such higher institutions are unacquainted of clinical breast examination (CBE), the predictors, and early presentation of the tumor.…”
Section: Discussionsupporting
confidence: 86%
“…This study stated that, beyond two third of the study subjects revealed to have low overall knowledge toward risk factors, general knowledge, and clinical manifestations of the malignant tumor, which was similar with the reports from Malaysia, Saudi, Egypt, and Nigeria (21, 26–28). Many female students in such higher institutions are unacquainted of clinical breast examination (CBE), the predictors, and early presentation of the tumor.…”
Section: Discussionsupporting
confidence: 86%
“…The questionnaire was adapted and developed (by the deletion and adaptation of items and scales) from the literature (5,15,18,20,22,23,25,26,28,29,31,32).…”
Section: Methodsmentioning
confidence: 99%
“…that BC becoming a global health-care interest, many researchers have been conducted worldwide to explore female's beliefs and knowledge about BC, and investigate their awareness about BC (1,5,(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). Most of these studies were in developed countries; only Suleiman (1) studied the awareness and attitude toward BC in Jordan, and his results showed that the study sample (Jordan university female students) had an insufficient awareness of BC.…”
mentioning
confidence: 99%
“…WHO emphasizes that early diagnosis of breast cancer and appropriate treatment are the ideal and most appropriate strategies for controlling the disease in developing countries (11) . The method of BSE is considered one of the simplest approaches that enable women to detect breast cancer in its earliest stages, through encouraging them to recognize the natural anatomy and texture of their breasts in order to determine any abnormalities in the future (4,(10)(11)(12) . However, it is not recommended to rely on this procedure as an alternative to clinical breast examination, radiology or pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Although the national program for early detection of breast cancer was established in the Ministry of Health in 2001 (4) , local studies conducted by Iraqi researchers show that more than 40% of the cases diagnosed in Iraq are still detected in advanced stages (5)(6)(7)(8)(9) ; recommending further national efforts to reduce the progression of the disease. In developing countries in general, the absence of a comprehensive nationwide program to control that cancer is considered the main reason behind the delayed diagnosis and mortality resulting from the disease (10) .…”
Section: Introductionmentioning
confidence: 99%